Bitentaculate Cirratulidae (Annelida: Polychaeta) from the northwestern Pacific Islands with description of nine new species - Magalhães, Wagner F.; Bailey-Brock, Julie H. (Zootaxa, 2013)
Thirteen cirratulid species from the Hawaiian, Mariana and Marshall Islandsare described. Nine species are new to science: Aphelochaeta arizonae sp. nov., Aphelochaeta honouliuli sp. nov., Caulleriella cordiformia sp. nov., Chaetozone michellae sp. nov., Chaetozone ronaldi sp. nov., Monticellina anterobranchiata sp. nov., Monticellina hanaumaensis sp. nov., and Tharyx tumulosa sp. nov., from Oahu, Hawaii and Aphelochaeta saipanensis sp. nov., from Saipan in the Mariana Islands. Dodecaceria fewkesi and Monticellina nr. cryptica are newly recorded from the Hawaiian Islands. Dodecaceria laddi is widely distributed in the western Pacific and material collected from the Hawaiian, Mariana andMarshall islands is described. We provide SEM photographs for all species in addition to line drawings and methyl green staining pattern photographs for the new species.